2018
DOI: 10.1007/s00436-018-5867-x
|View full text |Cite
|
Sign up to set email alerts
|

Tick infestation and occurrence of Anaplasma phagocytophilum and piroplasms in cattle in the Republic of Serbia

Abstract: Ticks transmit important pathogens affecting cattle such as intracellular bacteria of the genus Anaplasma or protozoa of the order Piroplasmida. This study aimed at assessing tick species present on pastures and cattle and determining occurrence of the tick-borne pathogens Anaplasma phagocytophilum and Babesia spp. in cattle. During May and June 2013, ticks and EDTA blood were collected from 185 dairy cows at six locations in Serbia. Ticks were also collected directly from the pastures at four of these locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…PCR testing to investigate bovine piroplasmosis was conducted by Vasic and co-workers [ 65 ], who detected Theileria spp. in 5 out of 135 bovine blood samples from northern and central Serbia.…”
Section: South-eastern Europementioning
confidence: 99%
“…PCR testing to investigate bovine piroplasmosis was conducted by Vasic and co-workers [ 65 ], who detected Theileria spp. in 5 out of 135 bovine blood samples from northern and central Serbia.…”
Section: South-eastern Europementioning
confidence: 99%
“…Although previous studies indicate that dogs are exposed to the causative agent of canine anaplasmosis, there have been no confirmed cases of this disease in Serbia to date. A recent study conducted in dairy cows confirmed the presence of antibodies to A. phagocytophilum in 2.45% of the tested animals from the areas of Gruža and Požarevac (Vasić et al, 2018).…”
Section: Role Of Jackals and Foxes In The Epidemiology Of Tick-borne mentioning
confidence: 81%
“…Different prevalences of infections with Theileria sp. were detected in cattle from Europe, ranging between 3.70 and 79.1% ( 36 , 37 ), and the most common species identified was the group T. sergenti/T. buffeli/T.…”
Section: Discussionmentioning
confidence: 99%